2003
DOI: 10.4049/jimmunol.170.1.158
|View full text |Cite
|
Sign up to set email alerts
|

Critical Paracrine Interactions Between TNF-α and IL-10 Regulate Lipopolysaccharide-Stimulated Human Choriodecidual Cytokine and Prostaglandin E2 Production

Abstract: Increased production of PGs by gestational membranes is believed to be a principal initiator of term and preterm labor. Intrauterine infection is associated with an inflammatory response in the choriodecidua characterized by elevated production of cytokines and PGs. The precise physiological significance of enhanced choriodecidual cytokine production in the mechanism of preterm labor remains uncertain. These studies were undertaken to dissect the roles and regulation of endogenous cytokines in regulating PG pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 72 publications
(52 reference statements)
7
67
0
1
Order By: Relevance
“…It inhibits production of proinflammatory cytokines such as TNFα, IL-1β, IL-6 and IL-8 (71,72). In the present study, we observed a decrease in IL-10 after treating RAW 264.7 cells with DMA in the presence of LPS.…”
Section: Dma Inhibits the Transcriptional Activity Of Nf-κb But Not Asupporting
confidence: 66%
“…It inhibits production of proinflammatory cytokines such as TNFα, IL-1β, IL-6 and IL-8 (71,72). In the present study, we observed a decrease in IL-10 after treating RAW 264.7 cells with DMA in the presence of LPS.…”
Section: Dma Inhibits the Transcriptional Activity Of Nf-κb But Not Asupporting
confidence: 66%
“…To test this hypothesis, the role of D6 in two animal models of fetal loss associated with inflammatory conditions was investigated. The first model was based on the induction of a systemic inflammatory response in mice by LPS treatment (16), an animal model mimicking a clinical condition frequently associated with abortion and preterm delivery in humans (17). Injection of pregnant D6 Ϫ/Ϫ mice with LPS resulted in a significant increase in fetal loss frequency (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This response is amplified by LPS-induced uterine NK cell synthesis of IFN-␥ (47). Cytokine responses in decidual leukocytes are augmented by increased production of a range of inflammatory cytokines, including TNF-␣, IL-1, IL-6, and IL-12 in choriodecidual membranes (49) and placental trophoblast cells (50).…”
Section: Discussionmentioning
confidence: 99%